A STUDY ON THE PROBLEMS FACED IN DAIRYING BY DAIRY FARMERS OF ALAPPUZHA DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The present study entitled problems faced in dairying by dairy farmers of Alappuzha District was taken up with the objectives of work out, To study the feeding, breeding, health care and veterinary services problems faced by dairy farmer, to study the livestock manage mental constraints faced by dairy farmer and to study the marketing of milk constraints faced by dairy farmer. To achieve the above objectives a sample of 160 households were selected randomly from Alappuzha district. The present study random sampling method was adopted. Alappuzha district was selected as the universe of the present study. Questionnaire survey was used to collect primary data from the dairy farmer. The questions asked regarding the type of breed, feeding practices, housing, water availability, marketing of milk, land available for cultivation of fodder crops and veterinary services etc. A target sample size for the study was 160 dairy farmer having more than two milch animals. The respondents were selected randomly in Alappuzha district.